Equal employment for person with disabilities an assessment R.A. 7277 (Magna Carta for Disabled Persons) - Soriano, Ma. Julia Salud A.; Aganon, Marie E.; Amante, Maragtas S.V.; Teodosio, Virginia A.; Gatchalian, Jose C. (2008)
This study provides an assessment of Equal Employment Opportunities for Person switch Disabilities under R.A. 7277 commonly known as the :Magna Carta for the Disabled" in order to determine if the objectives of the legislation have been realized. This assessment has been carried out against a background of severe unemployment (13%) and underemployment (28%) affecting not only able-bodied workers but also Persons with Disabilities(PWDs). More other than segments of the population, evidence showed that PWDs lacked employment opportunities and are likely to remain economically independent on their families and on social services provided by non-government organizations or charity. Research also showed that the most common misconception about disabled workers is that they are unable to work due to their physical impairments. They are disqualified members of mainstream society and of the working population in general, albeit deserving recipients of social security benefits and special employment schemes/subsidies. Equality is generally defined as treating everyone irrespective of race, gender, religion and disability. As such, persons with disabilities are not impaired by their disability but by the contours, perceptions and attitudes of society at large. Equality, Social Justice and Equal Employment opportunities for disabled persons are the cornerstone of Republic Act No. 7277.To implement the articulated intentions of this law, various agencies were tasked to create policies and programs that hope to advance the welfare of PWDs. These agencies include the Department of Education, Culture and Sports (DepEd), ,Department of Labor and Employment (DOLE), Department of Social Welfare and Development (DSWD), Department of Public Works and Highways (DPWH), the National Council for the Welfare of Disabled Persons (NCWDP) and local government units....
"March 2008."
Thesis (M.S. Industrial Relations)--University of the Philippines Diliman.
Keywords: People with disabilities -- Employment; Federal aid to services for people with disabilities; Magna Carta for Disabled Persons (Republic Act 7277).